Eiders, nutrients and eagles: Bottom-up and top-down population dynamics in a marine bird_dataset ... - Morelli, Federico; Laursen, Karsten; Svitok, Marek; Benedetti, Yanina; Pape Møller, Anders (Dryad, 2021)
The main objective of this long-term study (1978-2016) was to find the underlying factors behind the declining trends of eider Somateria mollissima in the Baltic/Wadden Sea. Specifically, we aimed at quantifying the bottom-up effect of nutrients, through mussel stocks, on reproduction and abundance of eider, and the top-down effects caused by white-tailed eagle Haliaeetus albicilla predation. Bottom-up effects increase marine primary productivity with subsequent effects on food availability for a major mussel predator. Top-down effects may also regulate eider populations because during incubation female eiders are vulnerable to predation by eagles. Our structural equation modelling explained a large percentage of the variance in eider abundance. We conclude that the Baltic/Wadden Sea eider population was regulated directly by white-tailed sea-eagle predation on incubating females and indirectly by the amount of nutrients in seawater affecting both mussel stocks and the breeding success of eiders, reflecting ... : Eider numbers Due to lack of long-term estimates of the Baltic/Wadden Sea eider population the Danish eider bag during 1960-2003 was used as a proxy for population size. After 2003, the open season was shortened, and thus not comparable to population size. The eider bag increased from 93,000 individuals in 1960 to a maximum of 190,300 in 1982, followed by a decrease to 75,200 in 2003. It is mandatory for hunters in Denmark to report their bag after each hunting season, and in most years, more than 85% of all hunters report the bag. Detailed information includes assessment of reliability by Strandgaard and Asferg (Strandgaard & Asferg 1980) and by Christensen and Hounisen (Christensen & Hounisen 2014). Significant positive correlations between the Danish eider bag and counts of eiders in Finland, Sweden and at migration sites is given in ESM (S1). Breeding success of eider The ratio of juveniles to the number of adult females in wing samples reported by hunters under the Danish Wings Survey scheme was ...